Abdominal aortic calcification is associated with a higher risk of injurious fall-related hospitalizations in older Australian women. (July 2021) - Gebre, Abadi K.; Sim, Marc; Rodríguez, Alexander J.; Hodgson, Jonathan M.; Blekkenhorst, Lauren C.; Szulc, Pawel; Bondonno, Nicola; Zhu, Kun; Bondonno, Catherine; Kiel, Douglas P.; Schousboe, John T.; Prince, Richard L.; et al.
Abstract: Backgrounds and aims: Abdominal aortic calcification (AAC) is associated with weaker grip strength, an established risk factor for fall-related hospitalizations. However, its association with long-term fall-related hospitalisations remains unknown. This study investigated the association between AAC and long-term fall-related hospitalizations in community-dwelling older women. Methods: Fall-related hospitalizations were obtained from linked data over 14.5-years in a prospective cohort of 1053 older women (mean age 75.0 ± 2.6 years). At baseline (1998/99), AAC was assessed from lateral spine images obtained using dual-energy X-ray absorptiometry, and scored using a semi-quantitative method (AAC24, range 0–24). The presence of any AAC was defined by AAC24 ≥ 1. Results: Over 14.5-years, 413 (39.2%) women experienced a fall-related hospitalization. In the multivariable-adjusted model, each unit increase in baseline AAC24 was associated with a 3% increase in relative hazards for a fall-related hospitalization (HR 1.03 95%CI, 1.01 to 1.07). Compared to women with no AAC, women with any AAC had a 40% (HR 1.40 95%CI, 1.11 to 1.76) and 39% (HR 1.39 95%CI, 1.10 to 1.76) greater risk for fall-related hospitalizations in the minimal and multivariable-adjusted models, respectively. This relationship was not attenuated by including measures of muscle function such as grip strength and timed-up-and-go. Conclusions: The presence of AAC is associated with long-term fall-related hospitalizations risk, independent of muscle function, in community-dwelling older women. Concurrent assessment of AAC may be a simple and cost-effective way to identify older women at higher risk of falling as part of routine osteoporosis screening. Graphical abstract: Image 1 Highlights: Abdominal aortic calcification (AAC) is associated with greater relative hazard of injurious fall-related hospitalizations. Including muscle function measures did not modify the association. AAC may be used to identify older women predisposed to falling.